The SAVI Learning Model and the 21st Century Skills: Developing Critical Thinking, Collaboration, and Creativity in Students Vocational High School - Taufiq Natsir; A. Ramli Rasyid; Samuel Akpan Bassey (Three E Science Institute, 2023)
The use of the SAVI learning model offers a more effective alternative in improving student learning outcomes by understanding individual learning preferences and providing learning strategies that follow the objectives of this study, namely to evaluate the use of the SAVI learning model for vocational high school students. The research approach used in this study is quantitative, using numbers and statistical analysis. The research design used was pre-experimental in a one-group pretest-posttest design. The present research study focused on the student population enrolled in vocational high schools in Makassar, Indonesia. Purposive sampling was used to select the most suitable sample for achieving the research objectives. The sample size consisted of 30 students, 25 of whom were male and five females. The SPSS Program enters data, performs statistical analysis, and visualizes the research results. The hypothesis test is tested at a significance level of 5% or 0.05. The results of testing the hypothesis using the SPSS application with the paired sample t-test data analysis technique obtained a significance of 0.000 where 0.000 < 0.05, which means that H0 is rejected and H1 is accepted. The analysis results prove that student learning outcomes (post-test) have increased compared to (pre-test). The SAVI learning model is more efficacious than traditional learning approaches, as it affords students a more engaging, enjoyable, and enduring educational encounter. It can serve as a pragmatic substitute for enhancing the caliber of education and students' academic achievements.